Patients' views on the causes of their polymyalgia rheumatica: a content analysis of data from the PMR Cohort Study. Issue 1 (25th January 2017) - Tshimologo, Maatla; Saunders, Benjamin; Muller, Sara; Mallen, Christian D; Hider, Samantha L
Abstract : Objective: To explore primary care polymyalgia rheumatica (PMR) patient beliefs about the causes of their PMR. Design: Qualitative content analysis was conducted on patients' written responses to the question of what they thought had caused their PMR. All data were coded and emergent categories of causal beliefs identified. Setting: Community patients receiving primary care at general practitioner (GP) practices across England. Participants: Participants were recruited from a primary care PMR inception cohort (n=654). Between June 2012 and June 2014 GPs referred 739 people with a new PMR diagnosis in the past 3 years into the study. Patients were mailed a baseline self-completion questionnaire, which included the question, 'What do you think caused your PMR?'. Responses to this question form the data set for the present study. Results: 296 (45%) patients gave a possible cause for their PMR, while 276 (42%) respondents wrote 'no idea'. Common attributions include ageing (45, 18%), medication (18, 5%) and personal stress (53, 14%). 24 respondents (6%) thought their PMR was as a result of another medical condition. Conclusions: This is the first study to examine causation beliefs in PMR, identifying a number of possible causes such as ageing, stress and as a complication of other medical problems. Understanding these patient beliefs may impact on treatment adherence and patient outcome.